Pemanfaatan MATLAB dalam Penentuan Koefisien Prediksi Frekuensi f0F2 - Budiyanto Budiyanto (Institut Teknologi Bandung, 2002)
Coefficients of empirical relation between f0F2 frequency of the ionospheric layer and the sunspot number R for an observatory at (ϕ,λ) can be easily and quickly determined by using MATLAB.